Utilization of life feed Alona sp., Boiled Egg Yolk and Commercial Feed Toward Survival Rate of Betta Fish Larvae (Jurnal Ilmiah PLATAX, 2019)
The purpose of this study was to find out the survival rates of betta fish larvae (cupang) that were given life feed Alona sp., boiled egg yolk and commercial feed for 21 days. Data analysis was performed by one-way ANOVA, and continued with BNJ (Tukey) test. The result of the survival rate is as follow treatment with life feed Alona sp. 56%, treatment with boiled egg yolk 26%, and treatment with commercial feed 0%. The results of statistical tests show there are significant differences.Â  Significant value p